Area-Performance Trade-offs in Tiled Dataflow Architectures - Swanson, Steven; Putnam, Andrew; Mercaldi, Martha; Michelson, Ken; Petersen, Andrew; Schwerin, Andrew; Oskin, Mark; Eggers, Susan J. (Proceedings of the 33rd Annual International Symposium on Computer Architecture, 2006)
Tiled architectures, such as RAW, SmartMemories, TRIPS, and WaveScalar, promise to address several issues facing conventional processors, including complexity, wire-delay, and performance. The basic premise of these architectures is that larger, higher-performance implementations can be constructed by replicating the basic tile across the chip. This paper explores the area-performance trade-offs when designing one such tiled architecture, WaveScalar. We use a synthesizable RTL model and cycle-level simulator to perform an area/performance pareto analysis of over 200 WaveScalar processor designs ranging in size from 19mm2 to 575mm2 and having a 22 FO4 cycle time. We demonstrate that, for multi-threaded workloads, WaveScalar performance scales almost ideally from 19 to 101mm 2 when optimized for area efficiency and from 44 to 202mm2 when optimized for peak performance. Our analysis reveals that WaveScalar's hierarchical interconnect plays an important role in overall scalability, and that WaveScalar achieves the same (or higher) performance in substantially less area than either an aggressive out-of-order superscalar or Sun's Niagara CMP processor.